Bicuspid Aortic Valve, from the Unknown till the Perfection of the Species - Marta Bargagna; Guido Ascione; Edoardo Zancanaro; Francesco Fioravanti; Alessandra Sala; Cinzia Trumello; Guohao Chang; Alessandro Verzini; Alessandro Castiglioni; Francesco Maisano (Reviews in Cardiovascular Medicine, 2024)
The bicuspid aortic valve (BAV) is the most common congenital cardiac abnormality. Though most often isolated, BAV may be associated with other cardiovascular malformations. BAV-related aortopathy is the most common, sharing genetic alterations and phenotypic heterogeneity characteristics. Sometimes silent for a lifetime, BAV may manifest as aortic valve dysfunction, aortic aneurysm, or more emergent situations, such as endocarditis or aortic dissection. Its embryological origin and the characterization of the genes involved, as well as the histopathological and hemodynamic aspects of its natural history, are becoming increasingly clear. In addition, emerging evidence of rhythm disorders associated with BAV has been identified. A new international nomenclature and classification has been introduced to interpret all the advances made in recent years for the comprehension of this condition. In the guidelines, more attention has been paid to the diagnosis of BAV and related aortopathy, together with surveillance, and family screening. Surgical treatment remains the gold standard, especially in young low-risk patients, and valve repair techniques have been shown to be effective and durable. Finally, the new era of transcatheter techniques is also being applied to dysfunctional BAV, allowing the treatment of patients at high surgical risk, with increasingly promising results, and the possibility of expanding indications through the introduction of more advanced devices. This review aims to comprehensively describe the BAV conundrum, focusing on anatomy, pathophysiology, genetics, diagnosis of BAV-related disorders, and the different treatment options available in the transcatheter era.